Metabolic fate of endogenous molecular damage: Urinary glutathione conjugates of DNA-derived base propenals as markers of inflammation - Watthanachai Jumpathong (2018)
© 2015, National Academy of Sciences. All rights reserved. Although mechanistically linked to disease, cellular molecules damaged by endogenous processes have not emerged as significant biomarkers of inflammation and disease risk, due in part to poor understanding of their pharmacokinetic fate from tissue to excretion. Here, we use systematic metabolite profiling to define the fate of a common DNA oxidation product, base propenals, to discover such a biomarker. Based on known chemical reactivity and metabolism in liver cell extracts, 15 candidate metabolites were identified for liquid chromatography-coupled tandem mass spectrometry (LC-MS/MS) quantification in urine and bile of rats treated with thymine propenal (Tp). Analysis of urine revealed three metabolites (6% of Tp dose): thymine propenoate and two mercapturate derivatives of glutathione conjugates. Bile contained an additional four metabolites (22% of Tp dose): cysteinylglycine and cysteine derivatives of glutathione adducts. A bis-mercapturate was observed in urine of untreated rats and increased approximately threeto fourfold following CCl4-induced oxidative stress or treatment with the DNA-cleaving antitumor agent, bleomycin. Systematic metabolite profiling thus provides evidence for a metabolized DNA damage product as a candidate biomarker of inflammation and oxidative stress in humans.